Bridging Gender Gaps? The Rise and Deceleration of Female Labor Force Participation in Latin America: An overview - Leonardo Gasparini; Mariana Marchionni (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2015)
This book contributes to the understanding of female labor force participation in Latin America by documenting the changes that took place over the last two decades, exploring their determinants, analyzing their consequences on labor and social outcomes, and discussing implications for public policy. The book highlights a potentially worrisome finding: after around half a century of sustained growth, there are signs of a widespread and significant deceleration in the entry of women into the Latin American labor markets. A version of this paper will be published as Chapter 1 of Gasparini and Marchionni (eds.) (2015). Bridging gender gaps? The rise and deceleration of female labor force participation in Latin America.
Keywords: 330